AN ANALYSIS OF THE IMPLEMENTATION OF GENDER MAINSTREAMING IN THE PLACEMENT OF FEMALE POLICE OFFICERS AS COMPETENCY-BASED SECTOR POLICE CHIEFS IN THE METRO JAYA POLICE - Yuliani Sariwaty Siregar; Nurliah Nurdin; Firman Hadi Rivai (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to analyse the gender mainstreaming of the Polri (Police of Indonesia Republic) at The Polda Metro Jaya (Province of DKI Jakarta Police) through the placement of policewomen as leaders in the Kapolsek (Region Sector Police) with the Indonesian social culture which still believes that a woman's duty is to take care of the household so that it does not give women the freedom to have a career, as well as the profession of policewomen by the public is seen as only part of the image of the police, where the presence of policewomen as a complement in the implementation of police duties and only placed in the functions of staff, personal secretary and administration. This research uses descriptive qualitative method by conducting interviews and field observations. Based on the research, there has been a policy in the framework of gender mainstreaming by placing female police officers as leaders in the police sector (Kapolsek) and there is no difference in the placement between female police officers and male police officers as police chiefs, but the successful implementation of gender mainstreaming has not been maximally implemented due to the lack of motivation of female police officers due to the challenges of police duties at The Metro Jaya Police which are quite complex and heavy police work dominantly related to crime cases and influenced by population density and territory as well as religious/community leaders in the police sector (Polsek) so that it requires the police chief to be ready to carry out 24-hour tasks to maintain security and order in the community.